2020
DOI: 10.2147/amep.s268315
|View full text |Cite
|
Sign up to set email alerts
|

<p>Knowledge, Attitude and Practice of Physicians Regarding Screening of Colorectal Cancer in Qatar: A Cross-Sectional Survey</p>

Abstract: The aim of this study was to evaluate the rate of internal medicine residents' and faculties' (specialists and consultants) compliance to colorectal cancer screening in Hamad Medical Corporation (Doha, Qatar) and to identify barriers as well as facilitators that will assist in drawing up changes that would enhance physician-related cancer screening. Methods: A cross-sectional web-based survey was distributed among internal medicine physicians at three component hospitals of Hamad Medical Corporation (HMC); foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…We read with great interest the original research article “Knowledge, Attitude and Practice of Physicians Regarding Screening of Colorectal Cancer in Qatar: A Cross-Sectional Survey”. 1 As practicing surgeons in the UK, it was interesting to consider whether the poor compliance and recommendation is actually to be expected from internal medicine physicians?…”
Section: Dear Editormentioning
confidence: 99%
“…We read with great interest the original research article “Knowledge, Attitude and Practice of Physicians Regarding Screening of Colorectal Cancer in Qatar: A Cross-Sectional Survey”. 1 As practicing surgeons in the UK, it was interesting to consider whether the poor compliance and recommendation is actually to be expected from internal medicine physicians?…”
Section: Dear Editormentioning
confidence: 99%
“…A third study in the West Pacific Region reported a low level of patient awareness of the disease burden and poor adherence to screening [ 12 ]. The frequency of non-compliance is reported to be even higher in developing countries either due to lack of awareness [ 13 ], patients’ refusal due to cultural barriers, financial burden [ 14 ], or non-referral by healthcare providers [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The participants in large numbers of the previous researches that were done in KSA were from shopping centers that are not illustrative the general public, furthermore, the questionnaire was used to assess the knowledge about CRC is unsubstantiated [3]. Factors including socialclass, individuals' beliefs, application of preventive care, healthcare access and background of cancer and screening tests and guidelines, considers as Barriers to Colorectal cancer screening [5].…”
Section: Introductionmentioning
confidence: 99%